Sphingosine kinase‐2 is overexpressed in large granular lymphocyte leukaemia and promotes survival through Mcl‐1. (2nd March 2020) - LeBlanc, Francis R.; Pearson, Jennifer M.; Tan, Su‐Fern; Cheon, HeeJin; Xing, Jeffrey C.; Dunton, Wendy; Feith, David J.; Loughran, Thomas P.
Summary: Sphingolipid metabolism is increasingly recognised as a therapeutic target in cancer due to its regulation of cell proliferation and apoptosis. The sphingolipid rheostat is proposed to control cell fate through maintaining balance between pro‐apoptotic and pro‐survival sphingolipids. This balance is regulated by metabolising enzymes involved in sphingolipid production. One such enzyme, sphingosine kinase‐2 (SPHK2), produces pro‐survival sphingosine 1‐phosphate (S1P) by phosphorylation of pro‐apoptotic sphingosine. Elevated SPHK2 has been found in multiple cancer types and contributes to cell survival, chemotherapeutic resistance and apoptosis resistance. We have previously shown elevation of S1P in large granular lymphocyte (LGL) leukaemia serum and cells isolated from patients. Here, we examined SPHK2 expression in LGL leukaemia and found SPHK2 mRNA and protein upregulation in a majority of LGL leukaemia patient samples. Knockdown of SPHK2 with siRNA in LGL leukaemia cell lines decreased proliferation. Additionally, the use of ABC294640 or K145, both SPHK2‐specific inhibitors, decreased viability of LGL leukaemia cell lines. ABC294640 selectively induced apoptosis in LGL cell lines and freshly isolated LGL leukaemia patient cells compared to normal controls. Mechanistically, SPHK2 inhibition downregulated pro‐survival myeloid cell leukaemia‐1 (Mcl‐1) protein through proteasomal degradation. Targeting of SPHK2 therefore provides a novel therapeutic approach for the treatment of LGL leukaemia.